2020
DOI: 10.1186/s12883-020-01911-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel RAB39B mutation and concurrent de novo NF1 mutation in a boy with neurofibromatosis type 1, intellectual disability, and autism: a case report

Abstract: Background: Mutations in RAB39B at Xq28 causes a rare form of X-linked intellectual disability (ID) and Parkinson's disease. Neurofibromatosis type 1 (NF1) is caused by heterozygous mutations in NF1 occurring de novo in about 50% of cases, usually due to paternal gonadal mutations. This case report describes clinical and genetic findings in a boy with the occurrence of two distinct causative mutations in NF1 and RAB39B explaining the observed phenotype. Case presentation: Here we report a 7-year-old boy with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…As an evolutionarily conserved vesicle transporter regulator group, Rab proteins localize to different membrane structures to regulate vesicle trafficking ( Corbeel and Freson, 2008 ). Recent studies have found that loss-of-function RAB39B mutations are associated with various diseases including XLID, autistic spectrum disorder (ASD), and Parkinson’s disease (PD) ( Supplementary Table 1 ; Giannandrea et al, 2010 ; Mata et al, 2015 ; Guldner et al, 2016 ; Lesage et al, 2016 ; Shi et al, 2016 ; Ciammola et al, 2017 ; Woodbury-Smith et al, 2017 ; Santoro et al, 2020 ). However, the physiological functions of RAB39B as well as its pathological roles in disease pathogenesis remain largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…As an evolutionarily conserved vesicle transporter regulator group, Rab proteins localize to different membrane structures to regulate vesicle trafficking ( Corbeel and Freson, 2008 ). Recent studies have found that loss-of-function RAB39B mutations are associated with various diseases including XLID, autistic spectrum disorder (ASD), and Parkinson’s disease (PD) ( Supplementary Table 1 ; Giannandrea et al, 2010 ; Mata et al, 2015 ; Guldner et al, 2016 ; Lesage et al, 2016 ; Shi et al, 2016 ; Ciammola et al, 2017 ; Woodbury-Smith et al, 2017 ; Santoro et al, 2020 ). However, the physiological functions of RAB39B as well as its pathological roles in disease pathogenesis remain largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…These variants lead to different changes in DNA methylation patterns, which may provide a link between chromatin remodeling, DNA methylation, and gene expression during development. RAB39B 17 encodes the Rab family. Rab proteins are small GTPases involved in vesicle transport.…”
Section: Discussionmentioning
confidence: 99%
“…A significant volume increase is observed in midline structures, with particular reference to the corpus callosum which looks altered both in terms of micro- and macro-structural measurements [ 37 , 40 ]. Subcortical structures, such as the hippocampus, amygdala and basal ganglia (i.e., thalamus and striatum), can also present larger volumes than normal [ 23 , 41 , 42 , 43 , 44 ]. Conversely, grey matter density is lower in the frontal parietal and temporal lobes (and, to a lesser extent, in cingulate and insular regions) with simplified cortical gyration and abnormal cortical thickness that decreases with age [ 18 , 23 , 45 , 46 ].…”
Section: Brainmentioning
confidence: 99%
“…Symptoms are usually represented by acute-onset focal neurological deficits with sudden weakness or numbness in the face, arm or leg on one side; other possible manifestations also include headaches, visual disturbances, developmental delay and seizures [ 76 ]. Among phakomatoses, NF1 has been suggested as a possible MMS predisposing disorder, and few susceptibility genetic loci have been recently identified [ 43 , 77 ]. This is why, despite the fact that MMS was usually described as a consequence of cranial radiation therapy for NF1-related optic pathway glioma, the majority of cases have been reported as a primary manifestation of NF1 even in the absence of previous radiotherapy [ 71 , 78 ].…”
Section: Brainmentioning
confidence: 99%